Sedução, trauma e tradução nas vivências de abuso sexual incestuoso : psicanálise e literatura de testemunho - Ferreira, Mariane Zanella (2015)
The goal of this research is to discuss some of the possibilities of translating experiences of incestuous sexual abuse analyzing two autobiographies written and published by women with sexual abuse history performed by their fathers: L'amore di papa: una storia vera (2013), by Pola kinski, and A Violação do Silêncio (1986/1988), by Eva Thomas. These autobiographies will be analyzed according to the theoretical and conceptual assumptions as given by the General Theory of Seduction (TSG in Portuguese), by Laplanche (1987/1992). This research emerged and was developed inside the Laboratory of Study and Research in Psychoanalysis and Civilization (LEPPSIC in Portuguese), as part of an overall research concerning current trauma and traumatic neurosis, after Freud, under TSG's perspective. Given the theoretical baselines, the discussion involves the aspects of the messages conveyed in an incestuous sexual abuse situation, as well as the possibilities of translation/repression of the enigmas associated to these messages. The analysis of the narratives allows the thinking of possible destinations for the drive-less overflow which invades psyche on the traumatic situation, such destination that depend, above all, on the psychic and social resources that each and every one has or can engineer to deal with trauma. Finally, it is proposed that, in the cases of incestuous sexual abuse covered here, guilt appears as the first translation for the excess, which fosters some psychic organization, but causes great suffering. More elaborated translations are possible coming from the de-translation of guilt and from the passivity elaboration in which the person is thrown in the traumatic situation that alludes to the original passivity. However, that translation is never complete, for we are always passive in front of the drive's attack.